Audiovisual translation in China: A dialogue between Yves Gambier and Haina Jin - Yves, Gambier; Jin, Haina (Journal of Audiovisual Translation, 2018)
This dialogue was conducted between Yves Gambier and Haina Jin in April and November 2017, and April 2018 in Beijing, China, in order to give a panoramic view of audiovisual translation in China today, the history of which dates back to the silent film era. Audiovisual translation has played an important role in cross-cultural communication, industrial development and social integration in China. Vibrant audiovisual translation activities can be seen in three main directions: translating foreign audiovisual products into Chinese, translating Chinese audiovisual products into foreign languages and audiovisual translation into ethnic minority languages in China. In this dialogue, the three main translation directions, the status of translators, the role of associations, standards, education and training, as well as further development of audiovisual translation in China will be discussed.